Development of Graphical User Interface for Link Budget Analysis of Point-to-Point Communications at 5 GHz and 11 GHz - Konstantinos Zarkadas; Apollon Smyrnaios; George Dimitrakopoulos (Network)
It is well known that simulation tools are essential for the design and optimization of wireless communication systems. This paper proposes a Python script that can be used for planning and predicting a connection link budget by analyzing its basic parameters. Our proposal consists of an application that calculates the connection budget for point-to-point links operating at 5 GHz and 11 GHz, taking into account all the necessary microwave parameters. For validating the efficiency of the proposed tool, this paper presents comprehensive simulation results derived from comparing our tool to a couple of other simulation tools by means of calculating the same parameters.